دلالة السياق القرآني في تفسير سورة الفاتحة عند المحقق سعيد بن خلفان الخليلي = The significance of the Qur’anic context in the interpretation of Surat Al-Fatiha according to the investigator Saeed bin Khalfan Al-Khalili - Ali Waleed Al-Hinai, Badriya; Elatrash, Radwan Jamal Yousef (Karabuk University, 2023)
يهدف هذا البحث إلى التعريف بمنهجية المحقق سعيد بن خلفان الخليلي العالم الفقيه الأصولي العماني حيث يعد من الشخصيات المهمة في دراسة علوم القرآن خلال القرن الثالث عشر الهجري، حيث تميز باهتمامه البالغ بعلوم القرآن وتفسيره، وقدم جهدًا كبيرًا في تفسير سورة الفاتحة والتي تعتبر من أعظم السور في القرآن الكريم. ومن معالم منهجية المحقق الخليلي في تفسير سورة الفاتحة استخدام أسلوب الدلالة اللغوية واعتمد على السياق والأسلوب الإشاري، وبهذا قدم تفسيرًا شاملًا يستخلص منه مضامين إيمانية توجه المسلمين في أداء واجباتهم الدينية. وقد كتب رسالة في تفسير سورة الفاتحة موجودة ضمن الجزء الثالث عشر من كتابه "تمهيد قواعد الإيمان وتقييد شوارد مسائل الأحكام والأديان"، مستخلصاً مضامين إيمانية حيوية. وقد ارتأى الباحثان توظيف المنهج الاستقرائي والمنهج التحليلي للوصول إلى منهجية المحقق الخليلي في تفسير سورة الفاتحة التي حوت مضامين القرآن كله، ومما توصلا إليه على سبيل المثال: أن للفظ القرآني أثر على السياق، كما للسياق السابق واللاحق أثر في الوصول للهدايات القرآنية التي تُتخذ منهجاً لحياة إيمانية كما أرادها المولى عز وجل. وهكذا ظهر جلياً أن للمحقق سعيد بن خلفان الخليلي رؤية تكاملية تضم عدة دلالات في آن واحد لإيصال فحوى معنى الآيات الكريمة لتالي كتاب الله الحكيم. ***** The investigator Saeed bin Khalafan Al-Khalili is a scholar, jurist, and Omani fundamentalist. He paid great attention to the sciences of the Qur’an in the thirteenth century AH, and interpreted many Qur’anic verses and wrote a treatise on the interpretation of Surat AlFatihah, which is found in the thirteenth part of his book “Tamheed: Qawaeid Al'iiman”. He interpreted the mother of the book in a linguistic, contextual, and indicative way, extracting faith contents from what the verses guide to in the greatest surah that a Muslim needs to perform his five duties daily. And because of the nature of the research, the two researchers decided to employ the inductive analytical approach to reach the methodology of the investigator Al-Khalili in interpreting Surat Al-Fatihah, which contained the contents of the entire Qur’an. For example, they reached: That the Qur’anic word influences the context, as well as for the previous and subsequent context, an effect in reaching the Qur’anic guidance that adopts a methodology for a life of faith as God Almighty wanted. And so, it became clear that the investigator Saeed bin Khalafan Al-Khalili has an integrative vision that includes several connotations at one time to convey the essence of the meaning of the noble verses to the follower of the book of God Almighty.